1993
DOI: 10.3109/01913129309084038
|View full text |Cite
|
Sign up to set email alerts
|

Postembedding Ultrastructural in Situ Hybridization on Ultrathin Cryosections and LR White Resin Sections

Abstract: A method was developed for nonisotopic postembedding in situ hybridization (ISH) on ultrathin sections of frozen and of LR White resin-embedded material at the electron microscopic level. The method was successfully applied to detect Epstein-Barr virus (EBV) DNA in the P3HR1 human Burkitt's lymphoma cell line. Each of the steps in the procedure had to be optimized for successful ISH on the frozen and LR White sections. The most important conditions are described. Predigestion with proteinase K was only necessa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Bendayan et al (1984) have demonstrated elegantly that immunogold conjugates never enter the depth of a section but rather remain stuck at its surface, even when hydrophilic resins are used. Pretreatment of sections with etching reagents and digesting enzymes have been reported to improve hybridization efficiency in postembedding ISH (Morey 1995;Lin et al 1993;Mandry et al 1993;Puvion-Dutilleul and Pichard 1992;Wolber et al 1988). However, cell structures were damaged and nonspecific binding of gold particles increased, probably owing to surface roughness of sections engendered by etching (Yi et al 1995).…”
Section: Figurementioning
confidence: 99%
“…Bendayan et al (1984) have demonstrated elegantly that immunogold conjugates never enter the depth of a section but rather remain stuck at its surface, even when hydrophilic resins are used. Pretreatment of sections with etching reagents and digesting enzymes have been reported to improve hybridization efficiency in postembedding ISH (Morey 1995;Lin et al 1993;Mandry et al 1993;Puvion-Dutilleul and Pichard 1992;Wolber et al 1988). However, cell structures were damaged and nonspecific binding of gold particles increased, probably owing to surface roughness of sections engendered by etching (Yi et al 1995).…”
Section: Figurementioning
confidence: 99%